PERBANDINGAN LITERASI INFORMASI MAHASISWA PEMULA POLITEKNIK NEGERI BATAM - Septiana, Maryani; Wirangga, Aditya (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2019)
This study aims to compare the level of information literacy of first-year students across different studies offered by major at Polytechnic Negeri Batam. The method used is a descriptive quantitative approach through a questionnaire conducted to 93 respondents. The sampling method uses purposive sampling. This study takes ALA concept of information literacy which are standard 1 about to able to identify a personal need for information, standard 2 about can access current knowledge and idnetify gaps, standard 3 is about can construct strategies for location information and data and standard 5 is about can review research process and compare and evaluate information and data. The results of this study are that level of student’s information literacy are in Good level. This level get results are 54% of correspondents, 42% satisfactory, low is 3% and only 1% got very satisfactory. This mostly can be showed by how they can review research process, compare and evaluate information and data.